THE BOUNDARIES OF BEING IN THE EYES OF FRANZ KAFKA’S METAMORPHOSIS: A CREATIVE ADAPTATION BY ESAD´S DIGITAL ARTS AND MULTIMEDIA STUDENTS FOR FILM, ANIMATION AND GAMING - Quadros, Tomé Saldanha; Varzim, Marta (Design/Arts/Culture, 2025)
The presented Artwork projects evoking the centenary (2024) of Franz Kafka´s death developed at the end of last academic year 2023/2024 by College of Arts and Design (ESAD, Matosinhos - Portugal) and University of Design, Innovation and Technology University (UDIT, Madrid - Spain), centred its focus on creative storytelling production for film, animation and gaming. At the turn of the twenty-first century or pictorial turn, we are seeking to understand to what extent the realm of moving pictures establishes the tension between belief and disbelief, or the depicted real and the constructed reality, staging sentimental fabulations of being. The metaphor of the boundaries of being in-between Metamorphosis and primal scenes unfolds the need of debating filmic object´s post-mediation and its immersive experience today. After a century of history, cinema seen as an Art form - which depicts space, time and causality - is still today subject of constantly evolving, and wherein the diegetic world of the presented Artwork projects aims to foster critical thinking upon the Metamorphosis´ main protagonist Gregor Samsa major existential concerns, still new today.